Interoperability - Chris Berg (Internet Policy Review, 2024)
Interoperability describes the ability of systems to share services and resources with other systems. It is used in many fields - in the law, in communications and payments systems, in healthcare systems and in military alliances, to name a few - and describes a large number of characteristics from technical standards, to information architecture, to organisational governance. This glossary entry presents a topology of interoperability layers and presents some of the key economic and socio-technical concerns faced by interoperable systems.
Keywords: 300; Interoperability; Sociotechnical ecosystems; Standards